ORGANIZATIONAL AND LEGAL BASIS FOR THE USE OF AIRCRAFT IN THE AGRARIAN SECTOR OF UKRAINIAN ECONOMY - Baran, R. T.; Baran, L. M. (Science and Transport Progress, 2009)
The problem of determination of the principles of organizational and legislative basis of the use of aviation in Ukrainian agriculture is discussed in this article. An example of carrying out the aviation-and-chemical works in agriculture, their legislative providing and environmental safety of conduction is analyzed. The basic models of effective aviation works as well as forms of introducing the modifications and amendments into the laws in force from the viewpoint of economic safety of agricultural industry are offered.